The breach and termination of real estate contracts - Tuiro Layme, Axel Enrique (2022)
In real state contracts there are innumerable contingencies that affect contractual legal relations, so our legal system has provided for a variety of legal remedies to protect the legitimate interests and/or rights of person who may be affected. Resolutions are for the most part the generally applicable legal remedy, since they are the most affective remedy for such cases. The default that might arise for the creditor to decide to terminate the contract has several aspects and assumptions that we will try to clarify in this paper.